Susceptibility of the Formate Hydrogenlyase Reaction to the Protonophore CCCP Depends on the Total Hydrogenase Composition - Janik Telleria Marloth; Constanze Pinske (Inorganics, 2020)
Fermentative hydrogen production by enterobacteria derives from the activity of the formate hydrogenlyase (FHL) complex, which couples formate oxidation to H2 production. The molybdenum-containing formate dehydrogenase and type-4 [NiFe]-hydrogenase together with three iron-sulfur proteins form the soluble domain, which is attached to the membrane by two integral membrane subunits. The FHL complex is phylogenetically related to respiratory complex I, and it is suspected that it has a role in energy conservation similar to the proton-pumping activity of complex I. We monitored the H2-producing activity of FHL in the presence of different concentrations of the protonophore CCCP. We found an inhibition with an apparent EC50 of 31 µM CCCP in the presence of glucose, a higher tolerance towards CCCP when only the oxidizing hydrogenase Hyd-1 was present, but a higher sensitivity when only Hyd-2 was present. The presence of 200 mM monovalent cations reduced the FHL activity by more than 20%. The Na+/H+ antiporter inhibitor 5-(N-ethyl-N-isopropyl)-amiloride (EIPA) combined with CCCP completely inhibited H2 production. These results indicate a coupling not only between Na+ transport activity and H2 production activity, but also between the FHL reaction, proton import and cation export.